"Two results method" of critical velocity determination in swimmers - which two results? - Leko, G.; Ruzic, L.; Matkovic, B. R. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
By monitoring the corresponding values of the speed of swimming as well as heart-rate values, and the concentration of lactate in blood, the current conditioning status of a swimmer could be obtained. It has been determined that all results of a swimmers in front crawl swimming lie on the same straight line within the co-ordinate system. Since two points suffice to determine the straight line, it is possible to determine the straight line in question by means of two results. The equation of such a straight line produces the same value of ANT as in the 4 mmol/L of blood. Since "critical velocity" should physiologically correspond to the velocity at anaerobic threshold (ANT), we tried to provide an answer to the question whether this method might be used instead of the blood analysis applied to determine the ANT. The sample of examinees was comprised of 24 top Croatian swimmers, aged 14-24. First, the best results on 25, 50, 100, 200, 400 and 800m front crawl swimming were noted. Then the protocol for obtaining the critical velocity at 4 mmol/L blood lactate was performed. The protocol consisted of 5 x 300 metres front crawl swimming at 80,85, 90, 95 and 100% intensity (with pacer) with a 15-minute break. The blood sample was taken 1 minute after the completion of the task. The non-linear estimation of the lactate curve was done by the least square method according to the model of the third-degree curve. The speed of each swimmer at the blood lactate concentration of 4 mmol/L was assessed on the basis of such a curve. The approximation of straight lines was done on the basis of 6 results at various distances. The non-linear estimation of the lactate curve showed a very high correlation (r=0.937) between the values of ANT obtained by means of measuring the blood lactate concentration and by the indirect non-invasive method. Then, we tried to determine which pair of the results produced the regression line on which the velocity at ANT would deviate the least from the velocity at ANT measured by invasive method. We compared the results derived from all possible pair of distances. Even though that Wakayoshi and al (1992) suggested 200 and 400m pair we found that only the pair of the results in 50 and 400 m showed no statistical difference between the velocity at ANT obtained by invasive and by non-invasive method (p<0.05). This method has its limitations specially concerning the individual lactate threshold but the approximation of ANT based on proposed "two-results method" is accessible to each coach since no technical aids for its execution are necessary and it could be performed on the basis of competition results.